Life on the line: exploring high‐performance practices from an employee perspective. Issue 5 (29th January 2018) - Pass, Sarah
Abstract: Through a case‐based approach, this study addresses the call for employee‐focused research to help us understand whether the high‐performance causal chain is the result of discretionary effort or management control and work intensification. Findings highlight the role of the manager and workplace relationships and emphasise the need for 'good practice'.